2022
DOI: 10.1161/circulationaha.121.057709
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning of the Retina Enables Phenome- and Genome-Wide Analyses of the Microvasculature

Abstract: Background: The microvasculature, the smallest blood vessels in the body, has key roles in maintenance of organ health as well as tumorigenesis. The retinal fundus is a window for human in vivo non-invasive assessment of the microvasculature. Large-scale complementary machine learning-based assessment of the retinal vasculature with phenome-wide and genome-wide analyses may yield new insights into human health and disease. Methods: We utilized 97,895 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 107 publications
5
77
1
Order By: Relevance
“…These studies demonstrated that GWAS has great potential to reveal genes with a key role for modulating vascular properties and potential pathomechanisms, yet, due to their limited power, revealed at best the tip of the iceberg. Indeed, a recently published study [49] performed a GWAS on vascular density and fractal dimension extracted from 97 895 images across 54 813 participants from the UK Biobank [54], finding 7 and 13 loci associated with these traits, respectively. The most significant association with the vascular fractal dimension was found for a locus containing the OCA2 gene (p∼10 −80 ), while for the vascular density, the strongest associations were for MEF2C and GNB3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies demonstrated that GWAS has great potential to reveal genes with a key role for modulating vascular properties and potential pathomechanisms, yet, due to their limited power, revealed at best the tip of the iceberg. Indeed, a recently published study [49] performed a GWAS on vascular density and fractal dimension extracted from 97 895 images across 54 813 participants from the UK Biobank [54], finding 7 and 13 loci associated with these traits, respectively. The most significant association with the vascular fractal dimension was found for a locus containing the OCA2 gene (p∼10 −80 ), while for the vascular density, the strongest associations were for MEF2C and GNB3.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, genome-wide association studies (GWAS) have been used to link genes with phenotypes extracted from fundus images, such as vessel size [39,40], optic disc morphology [41,42], vascular density [43], fractal dimensions [43] and vessel tortuosity [44]. The diameter of the retinal microvasculature was associated with genes TEAD1, TSPAN10, GNB3 and OCA2 [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 A recent study using the UK Biobank data source in fewer participants (54,813 vs 65,144 in this study), showed that retinal vessel density and fractal dimensions (extracted from the entire image after deep learning vessel segmentation without distinction between arterioles and venules) were associated with other health outcomes, including overall mortality, hypertension and congestive heart failure, but did not report on risk predictionperformance. 41 Moreover, there was no consistent evidence of associations with incident circulatory disease, and cerebrovascular disease and associations with incident MI were null. 41 Another study in a sub-set of UK Biobank participants (n=5,663) with both retinal and cardiovascular magnetic resonance imaging used deep learning /AI approaches to estimate structural cardiac indices as intermediaries for predicting MI.…”
Section: Comparisons With Other Studiesmentioning
confidence: 98%
“…41 Moreover, there was no consistent evidence of associations with incident circulatory disease, and cerebrovascular disease and associations with incident MI were null. 41 Another study in a sub-set of UK Biobank participants (n=5,663) with both retinal and cardiovascular magnetic resonance imaging used deep learning /AI approaches to estimate structural cardiac indices as intermediaries for predicting MI. 42 However, given their approach, specific retinal features of importance remain unclear.…”
Section: Comparisons With Other Studiesmentioning
confidence: 98%